Three Approaches to the Evaluation of Active Labour Market Policy in East Germany Using Regional Data - Tobias Hagen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Using different regional data sources for East Germany the three largest active labour market policy (ALMP) programmes – job creation schemes (JCS), structural adjustment schemes (SAS) and public training (PT) – are evaluated. After addressing the regional allocation rule of the funding of ALMPs and the fundamental simultaneity problem in macroeconomic evaluation studies, identification strategies and possible instrumental variables are discussed. Three different approaches based on different econometric techniques for panel data (GMM and two-stage least squares) are applied. An augmented matching function indicates a negative effect of JCS on regional matching efficiency (inflows into regular employment) and no significant effects of PT and SAS. A reduced form approach based on the Beveridge curve does not indicate any long-term effects of ALMPs on regional job seeker rates. A dynamic labour demand estimation indicates that PT has no effects on employment and JCS leads to displacement of regular employment.
Keywords: H43; E24; J68; C33; 330; Evaluation; Active Labour Market Policy; Identification; Regional Data; Matching Efficiency; Crowding-out; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Regionaler Arbeitsmarkt; Regionale Arbeitslosigkeit; Crowding out; Beveridge-Kurve; Schätzung; Neue Bundesländer